Parasitism capacity of Telenomus remus and Trichogramma pretiosum on eggs of moth pests of peanut - Lima Pinto, Jose Ricardo [UNESP]; Fernandes, Odair Aparecido [UNESP] (Alma Mater Studiorum, Univ Bologna, 2020)
Telenomus remus Nixon (Hymenoptera Scelionidae) and Trichogramma pretiosum Riley (Hymenoptera Trichogrammatidae) are widely used for the control of lepidopteran pests in several countries, but applied programs using these parasitoids in peanuts are still rare. Therefore, the comparative parasitism capacity of T. remus and T. pretiosum in Stegasta bosqueella (Chambers) (Lepidoptera Gelechiidae), Spodoptera cosmioides (Walker) and Spodoptera frugiperda (J.E. Smith) (Lepidoptera Noctuidae) eggs were studied under controlled conditions (12L:12D photoperiod, 25 +/- 1 degrees C, and 70 +/- 10% RH). Eggs of S. bosqueella, S. cosmioides and S. frugiperda were offered daily throughout the adult lifespan of the parasitoids. Both parasitoids did not parasitize eggs of S. bosqueella. Eggs of Spodoptera spp. were significantly more parasitized by T. remus than by T. pretiosum. These two parasitoids presented the highest parasitism rate in the first 24 hours in Spodoptera eggs. However, to obtain 80% of parasitism in Spodoptera spp. took up to seven days for T. remus and up to three days for T. pretiosum. Telenomus remus demonstrated a longer lifespan, greater number of emerged parasitoids, and a female-biased sexual ratio, which might result in a greater potential control of Spodoptera spp. in the field. For S. bosqueella, other biological control agents should be considered.
Keywords: biological control; egg parasitoids; biological parameters